Penerapan Kualitas Bahan Baku Kayu Pada Usaha Meubel Warsito Desa Jayakarta, Bengkulu Tengah - suryani, reni; Hidayah, Nenden Restu; Susena, Karona Cahya (Jurnal Kewirausahaan dan Bisnis, 2023)
Warsito Furniture Business in Jayakarta Village, Bengkulu Tengah is one of the MSME industries. Starting from himself, Mr. Warsito made a furniture business called Warsito Furniture Business. This business was founded in 1998 with makeshift equipment. With high interest, this business began to develop and was eyed by the Social Welfare Service of Bengkulu Province. The Independent Family Joint Business Group (KUBE) "WARSITO was officially formed on January 1, 2001 and is located in Hamlet I Jayakarta Village, Talang Empat District, North Bengkulu Regency. In increasing the capacity and capability and productivity of the carpentry business, business owners are actively conducting job training with makeshift equipment to produce a quality product. Wood is the main element that determines the quality of a product of furniture or other wood crafts. Furniture was originally a craft industry that produced more artistic aspects. Products with good quality will provide satisfaction value for consumers or customers so that complaints from customer complaints after buying and using the products they buy can be avoided.To achieve the quality or quality as expected, the company must be able to know and apply how to choose the type of material that is good to manage and the factors that can affect the quality or quality of the product during the production process. Keywords: application, quality, wood, furniture, UMKN